KAJIAN HUTAN WISATA ALAM GUNUNG MEJA (HWAGM) SEBAGAI SUMBER PEMBELAJARAN PENDIDIKAN BERBASIS LINGKUNGAN ALAM: Sebuah Paradigma Baru Pendidikan Muatan Lokal Pada Era Otonomi Khusus Papua - Boari, Yunus; Martanto, Eko Agus; Sudjatno, Joko (Universitas Papua Manokwari, 2017)
The research was conducted in this area, which is administratively located in the district of Manokwari of West Papua province.The data is collected through interviews, field observations, and library research. The results showed that 1) NFGM area has potential as a source of natural learning environment-based education, 2) the potential for the region based on the characteristics NFGM comprising: a) resident owners of customary rights of local knowledge in the form of «Ayamfos» (NFGM areas should be protected, well maintained and utilized for the preservation. Local knowledge can be used as a model in the learning process, b) NFGM area has a diversity of flora and fauna are high, c) NFGM area has diverse soil resources both physical and chemical characteristics, varies, which affect the lives of flora and fauna. d) NFGM area has important sites such as the Japanese monument and caves. 3) The neighborhood revitalization strategy of NFGM is very important in order to restore function and preservation. The strategy consists of: a) conservation efforts of NFGM region, b) Provision of facilities and infrastructure to support the development and preservation of the area, c) conducting an intensive campaign to attract domestic and foreign tourists, d) formulate policies related to local curriculum which is based on education natural environment.